Risk Factors of Postoperative Nausea and Vomiting on General Anesthesia in RSUD Abdul Wahab Sjahranie Samarinda - Christopher Kevin Susanto; Eva Rachmi; Muhammad Rizqan Khalidi (Journal of Agromedicine and Medical Sciences, 2022)
Postoperative Nausea and Vomiting (PONV) is the nauseous feeling within 24 hours after surgery. PONV increases the risk of fluid and electrolyte imbalance, re-opening of the surgical wound, and aspiration of gastric fluid. This study aimed to analyze the effect of postoperative opioid administration, duration of anesthesia, type of surgery, and BMI on the incidence of nausea and vomiting after surgery under general anesthesia, at Abdul Wahab Sjahranie Hospital, Samarinda. The research design employed in this research was a retrospective cohort study. The number of samples was 92 patients. The results of the analysis showed an increased risk of PONV in underweight – normal BMI patients (1.45 times higher risk; p=0.035), patients who received postoperative opioids (1.64 times higher risk; p=0.005), patients who underwent surgery that was potentially stimulating the vagus nerve (1.52 times riskier; p=0.02), and patients with anesthetic duration of more than 2 hours (1.93 times greater risk; p=0.007). Therefore, it could be concluded that BMI, postoperative opioid use, type of surgery, and duration of anesthesia influenced PONV incident on the use of general anesthesia at RSUD Abdul Wahab Sjahranie, Samarinda. Keywords: postoperative nausea and vomiting, BMI, opioid after surgery, type of surgery, anesthesia duration